To complete the statement about the arithmetic sequence, we can use the information provided:
- The 3rd term of the sequence is \( a_3 = \frac{3}{2} \).
- The common difference is \( d = \frac{1}{2} \).
In an arithmetic sequence, the \( n \)-th term can be calculated using the formula:
\[ a_n = a_1 + (n-1)d \]
For the 3rd term, the formula would be:
\[ a_3 = a_1 + 2d \]
Substituting the known values:
\[ \frac{3}{2} = a_1 + 2 \left( \frac{1}{2} \right) \]
This simplifies to:
\[ \frac{3}{2} = a_1 + 1 \]
Now, solving for \( a_1 \):
\[ a_1 = \frac{3}{2} - 1 = \frac{3}{2} - \frac{2}{2} = \frac{1}{2} \]
Now that we have \( a_1 \), we can state:
- The first term of the arithmetic sequence is \( \frac{1}{2} \).
- The second term can be found by adding the common difference to the first term:
\[ a_2 = a_1 + d = \frac{1}{2} + \frac{1}{2} = 1 \]
To summarize:
The first term of the arithmetic sequence is \( \frac{1}{2} \), the second term is \( 1 \), and the third term is \( \frac{3}{2} \). The common difference is \( \frac{1}{2} \).
Complete statement: The first term of the arithmetic sequence is \(\frac{1}{2}\), and the second term is \( 1 \).